PENGARUH POLA HARI HUJAN TERHADAP PERKEMBANGAN PENYAKIT GUGUR DAUN CORYNESPORA PADA TANAMAN KARET MENGHASILKAN - Nurhayati dan Aron Situmorang . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2008)
Effect of weather on the development of leaf fall disease in the yielding rubber estate. This research was conducted in PTP VII Bergen Lampung from July to August for 2005 and 2006 (new leaves period). This research was carried out using survey and experiment methods. Parameters observed in the research were persentages of leaf stage, the number of leaf fall per m2 caused by Corynespora cassiicola and amount of spore distributed in air, daily rainfall amount and number of rain days. Results of the study showed that the pattern of rainfall and number of raindays affected the development of plant’s new leaves and leaf fall disease caused by Corynespora. The amount of spores distributed in the air was relatively higher in 2005 observation period compared to 2006 one. The pattern of rainfall and number of rain days also affected the disease severity which was higher in 2005 compared to 2006. Epidemy was occurred when lower rainfall amount taking place intermittently with sunny days in the period of new leave formation.